Policy interventions that attract nurses to rural areas: a multicountry discrete choice experiment. - Blaauw, D; Erasmus, E; Pagaiya, N; Tangcharoensathein, V; Mullei, K; Mudhune, S; Goodman, C; English, M; Lagarde, M (2010)
OBJECTIVE: To evaluate the relative effectiveness of different policies in attracting nurses to rural areas in Kenya, South Africa and Thailand using data from a discrete choice experiment (DCE). METHODS: A labelled DCE was designed to model the relative effectiveness of both financial and non-financial strategies designed to attract nurses to rural areas. Data were collected from over 300 graduating nursing students in each country. Mixed logit models were used for analysis and to predict the uptake of rural posts under different incentive combinations. FINDINGS: Nurses' preferences for different human resource policy interventions varied significantly between the three countries. In Kenya and South Africa, better educational opportunities or rural allowances would be most effective in increasing the uptake of rural posts, while in Thailand better health insurance coverage would have the greatest impact. CONCLUSION: DCEs can be designed to help policy-makers choose more effective interventions to address staff shortages in rural areas. Intervention packages tailored to local conditions are more likely to be effective than standardized global approaches.